Apache Hive Essentials : Essential Techniques to Help You Process, and Get Unique Insights from, Big Data, 2nd Edition. - Du, Dayong (Packt Publishing Ltd, 2018)
Apache Hive helps you deal with data summarization, queries, and analysis for huge amounts of data. This book will give you a background in big data, and familiarize you with your Hive working environment. Next you will cover advanced topics like performance and security in Hive and how to work efficiently to find solutions to big data problems.